Diet-microbiome interactions influence lung function in chronic obstructive pulmonary disease - Qiu, Haowen; Checketts, Rees; Jackson, Mariah Kay; Riethoven, Jean-Jack M.; Hansel, Nadia N.; Bailey, Kristina L.; Hanson, Corrine; Samuelson, Derrick R. (Frontiers in Microbiomes, 2024)
Chronic Obstructive Pulmonary Disease (COPD) affects 30 million Americans. Previous epidemiologic work has shown that diet can impact pulmonary function in those with and without COPD. Diet is also a major driver of gut microbiome composition and function. Importantly, the gut microbiome has also been associated with lung health (i.e., the gut-lung axis) in both preclinical and clinical studies. Despite this growing body of evidence, many questions remain regarding the gut-lung axis. Specifically, how the microbiome impacts the relationship between diet factors and spirometry or stage of disease in people with COPD is little understood. We hypothesize that there are taxonomic differences in the gut microbiome among the different stages of COPD and that diet microbiome interactions influence pulmonary function. This study aimed to identify how the GI microbiota correlated with the severity of respiratory disease in COPD patients and how the microbiome may mediate the relationship between diet, including fiber and omega-3 fatty acids, and lung function outcomes.